Pili Annulati Coincident with Alopecia Areata, Autoimmune Thyroid Disease, and Primary IgA Deficiency: Case Report and Considerations on the Literature - E. Castelli; S. Fiorella; V. Caputo (Karger Publishers, 2012)
Pili annulati is a rare autosomal dominant hair disorder clinically characterized by a pattern of alternating bright and dark bands of the hair, the bright bands appearing dark if observed by transmitted light. This pattern is due to the periodic occurrence of air-filled cavities along the hair cortex which scatter and reflect the light while precluding its transmission. A susceptibility region, including a possibly responsible Frizzled gene, has been mapped to the telomeric region of chromosome 12q, although a specific mutation has not been identified. The condition has sometimes been observed in concurrence with alopecia areata, and in this paper we report a case in whom the concomitant severe alopecia areata was associated with autoimmune thyroid disease and primary IgA deficiency - a quadruple complex which, to our knowledge, has never been previously described. The occurrence of multiple immune disorders in the same patient affected by pili annulati could represent a key to understanding the high prevalence of alopecia areata in this condition. Specifically, in individuals predisposed to autoimmune disease, the molecular alterations that cause the anatomical changes of pili annulati could prompt the immune response against the hair root that underlies alopecia areata.